An assessment of the sustainability of Living Labs in Kenya. Issue 4 (18th October 2019) - Ondiek, Mary Auma; Moturi, Christopher
Abstract : Purpose: There has been a high rate of failure among the Living Labs in Kenya resulting in the expected outcomes not fully realized. This paper aims to assess the sustainability of Living Labs in Kenya. Design/methodology/approach: Based on the four capital method of sustainable development evaluation framework, data were collected through interviews and questionnaires from innovators, users and employees among the 25 living labs in Kenya. Findings: The research found that some innovators are not familiar with the living labs, the living labs are innovative and prepared to survive in future, some labs have strategic plans on how to pursue future environment and have developed ways of choosing right people to incubate, inability to get enough funding from the host organizations and limited knowledge on the supervision level of the operations. A model is proposed that can be generalized to other living labs in developing countries. Research limitations/implications: The study was done in Nairobi where most of the living labs are situated. Practical implications: The study concludes by emphasizing on the user involvement during innovation process. There is need to expand the capacities of living labs to accommodate more people to ensure more innovations are supported at a time. The senior managers in charge of the living labs should increase the level of supervision to ensure that the labs are effective in their incubation efforts and institutionalize support of the host organization to the labs to ensure continued growth and expansion. Originality/value: The findings of this study are of value to research community, the decision and policymakers as it seeks to document the current status of the living labs in the Kenya